Peningkatan Calon Tunggal Dalam Pemilihan Kepala Daerah - Christya Putranti (Soegijapranata Catholic University, 2021)
Regional Leaders Election (Pilkada) is an interesting matter to discuss, Pilkada regulations have undergone several changes, the phenomenon of change occurs starting from the appointment of a regional head, in which was initially elected by House of Presentatives (DPR) until finally returned to the public as people's sovereignty, the enactment of Law No. 1 of 2015 concerning about the stipulation of Government Regulation in Lieu of Law (Perpu) No. 1 of 20114 which discussed about the Election of Governors, Regents and Mayors into a law which enforced the return of elections to be carried out by House of Presentatives which led to harsh criticism from the public so in the end government restored the public's right to vote. Another interesting thing is that as a result of the people's sovereignty, the right to be elected and to elect the citizens, especially in regions, must be implemented. Unfortunately, the problem this has become a new problem, which was the delay in the implementation of regional elections. In Law No. 32 of 2004 concerning about Regional Government in which only regulates that regional heads are proposed through a combination of political parties and political parties, after the decision of Constitutional Court Number 5 / PUU-V / 2007 individual candidates also can run for regional head candidates. Law Number 18 of 2015 had been reviewed by the Constitutional Court Number 100 / PUU-VIII / 2015. The blank ballot box regulation then appears in General Elections Commission Regulation (PKPU) Number 14 of 2015 concerning about the election for Governor and Vice Governor, Regent and Vice Regent and / or Mayor and Vice Mayor upon follow-up to the Constitutional Court decisions. This study will focus on the increasing blank ballot box that continues to increase, starting from a single candidate with “agree and disagree